Implementasi Kurikulum Merdeka Pada Mata Pelajaran Pendidikan Agama Islam - Sugiyanto, Sugiyanto; Budiyono, Ahmad; Fatikah, Noor; Jafar Sodik , M (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The Independent Curriculum is designed to provide flexibility in the teaching and learning process, allowing students to be more active and creative in exploring learning materials. The independent curriculum is a curriculum that was previously referred to as a prototype curriculum which was later developed as a more flexible curriculum framework, while focusing on essential materials and character development and student competencies. This study uses a qualitative method. The objectives of this study are: 1. How is the implementation of the independent curriculum in Islamic religious education subjects at SDN Kabuh Jombang?, 2. What are the problems in implementing the independent curriculum in Islamic religious education subjects at SDN Kabuh Jombang?. 3. How do teachers overcome problems in implementing the independent curriculum in Islamic religious education subjects at SDN Kabuh Jombang?. The results of the study show that: First, the implementation of the Independent Curriculum in Islamic Religious Education subjects at SDN Kabuh Jombang is carried out in three stages, namely Islamic Religious Education Teacher Preparation, Learning Implementation, and Learning Assessment. Second, the problems in implementing the Independent Curriculum include: a. Difficulty changing old mindsets or habits b. less than optimal implementation of differentiated learning. Three Teacher Solutions to Overcome Problems in Implementing the Independent Curriculum Several efforts to solve the problems include: a. Expanding knowledge related to learning methods b. Attending workshops